Silver Nanoparticles Increase Nitrogen, Phosphorus, and Potassium Concentrations in Leaves and Stimulate Root Length and Number of Roots in Tomato Seedlings in a Hormetic Manner - Gabriela Abigail Guzmán-Báez (SAGE Publishing, 2021)
Background Silver nanoparticles (AgNPs) display unique biological activities and may serve as novel biostimulators. Nonetheless, their biostimulant effects on germination, early growth, and major nutrient concentrations (N, P, and K) in tomato ( Solanum lycopersicum ) have been little explored. Methods Tomato seeds of the Vengador and Rio Grande cultivars were germinated on filter paper inside plastic containers in the presence of 0, 5, 10, and 20 mg/L AgNPs. Germination parameters were recorded daily, while early growth traits of seedlings were determined 20 days after applying the treatments (dat). To determine nutrient concentrations in leaves, a hydroponic experiment was established, adding AgNPs to the nutrient solution. Thirty-day-old plants were established in the hydroponic system and kept there for 7 days, and subsequently, leaves were harvested and nutrient concentrations were determined. Results The AgNPs applied did not affect germination parameters, whereas their application stimulated length and number of roots in a hormetic manner. In 37-day-old plants, low AgNP applications increased the concentrations of N, P, and K in leaves. Conclusion As novel biostimulants, AgNPs promoted root development, especially when applied at 5 mg/L. Furthermore, they increased N, P, and K concentration in leaves, which is advantageous for seedling performance during the early developmental stages.